Experimental Investigation on Wire Rope Isolators - Davis, Michael Tristan (IRC, 2020)
This dissertation experimentally investigates stiffness properties of wire rope isolators intended to serve as vibration dampeners in drones. Two designs of wire rope isolators has been fabricated (e.g. different wire diameters, number of wires, wire rope length) and put to test using universal tensile testing machine. The literature review needed for the project is completed. The methodology generally explains the steps taken during the experimental investigation of the wire rope isolators and how the data has been analysed. In the results, the stress-strain data along with the load-displacement data is analysed and plotted to differentiate the two wire rope isolators. From the plots, the stiffness characteristics is calculated and the data is used to apply the models to different stabilizer applications.